Some of the most important rulings of the constitutional court of Republic of Kosovo (Vallis Aurea, 2022)
Almost all countries with liberal democracies have established specialized courts whose primary function and paramount role fulfi l an extremely important role in the protection of human rights, interpretation and protection of the constitution as well as defi ning and promoting important principles such as the separationof powers, rule of law and the protection of minorities and other constitutional values. Constitutional courts utilizing case law and precedent have played pivotal roles in determining the constitutional identities of theirrespective states. Since its establishment, The Constitutional Court of the Republic of Kosovo(“CCK”or “TheCourt”) has been very active in its decision-making and has greatly infl uenced the defi nition and cultivationof the constitutional identity of Kosovo. Its decisions have defi ned important constitutional frameworks suchas the protection of human rights, protection of the rights of national minorities, separation of powers andunity of the state and many other important principles. It can be said that, in general, the Court has been theguardian of the Constitution and constitutional democracy, fulfi lling the main purpose of its establishment. This paper will address the jurisdiction and organization of the Constitutional Court of Kosovo, and some ofthe important decisions which have undoubtedly played an important role in determining the constitutionalidentity of the country.